Acute pancreatitis is associated with Ser608Leu iNOS polymorphism - Özhan, G; Sari, F M; Vefai, M; Yanar, H T; Alpertunga, B (Folia biologica, 2012)
Acute pancreatitis is an initially localized inflammation of the pancreatic gland. The precise mechanisms by which aetiological factors induce acute pancreatitis are not yet known, but when initiated, common inflammatory pathways seem to be involved, with cytokines being their components of major importance. The inducible nitric oxide synthase gene (iNOS) encodes an enzyme involved in the pathway of reactive oxygen species and induced in response to infection, cytokines. iNOS is capable of generating large quantities of nitric oxide produced during inflammation. The objective of this study was to investigate the association between acute pancreatitis risk and iNOS polymorphisms. The studied single-nucleotide polymorphisms (SNPs) were Ser608Leu, resulting in an amino acid substitution, and 1173C/T and 954G/C, both in the gene promoter region that is linked to increased enzyme expression, leading to higher NO production. The genotypes for the three SNPs were determined in 93 patients with acute pancreatitis and 60 controls without pancreatitis or cancer that were matched for age and gender. Data analysis was done by conditional logistic regression. It was found that the Ser608Leu polymorphism was more frequent among cases with acute pancreatitis compared to controls (OR = 2.88; 95% CI: 1.49-5.57; P = 0.002), although no individually statistically significant associations for the other SNPs studied were detected. We suggest that iNOS Ser608Leu can be used as a marker to define the risk of acute pancreatitis.
Keywords: Nitric Oxide Synthase Type II; pankreatitida; Amino Acid Substitution; Polymorphism, Single Nucleotide; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; jednonukleotidový polymorfismus; Female; rizikové faktory; Aged; frekvence genu; senioři; lidé; ženské pohlaví; Male; substituce aminokyselin; Middle Aged; synthasa oxidu dusnatého, typ II; Genetic Predisposition to Disease; genetická predispozice k nemoci; Gene Frequency; Pancreatitis; mužské pohlaví; Acute Disease; akutní nemoc; Risk Factors